2016
DOI: 10.1111/jir.12285
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for adults with mild intellectual disabilities and mental ill‐health: a systematic review

Abstract: There are few evidence-based interventions for people with mild intellectual disabilities and mental ill-health; existing literature is limited in quantity and quality. Group cognitive-behavioural therapies have some supporting evidence - however, further randomised control trials are required, with longer-term follow-up, and larger sample sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
3
44
0
1
Order By: Relevance
“…This is in line with much of the existing literature (Bhaumik, Gangadharan, Hiremath, & Russell, 2011;Hollins & Sinason, 2000;Sinason, 2002), despite the historical perception that people with ID do not stand to benefit from psychotherapy (see Beail, 2015). The current findings indicate the presence of a practical approach to treatment, in the absence of a sufficient evidence base (Osugo & Cooper, 2016;Vereenooghe & Langdon, 2013). Therapists working with this population, or researching this area in the future, may find it fruitful to focus on process factors highlighted in our study findings, for example, shame, power, trust, and validation.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with much of the existing literature (Bhaumik, Gangadharan, Hiremath, & Russell, 2011;Hollins & Sinason, 2000;Sinason, 2002), despite the historical perception that people with ID do not stand to benefit from psychotherapy (see Beail, 2015). The current findings indicate the presence of a practical approach to treatment, in the absence of a sufficient evidence base (Osugo & Cooper, 2016;Vereenooghe & Langdon, 2013). Therapists working with this population, or researching this area in the future, may find it fruitful to focus on process factors highlighted in our study findings, for example, shame, power, trust, and validation.…”
Section: Discussionsupporting
confidence: 89%
“…Historically, it has been argued that people with ID were unable to engage in cognitive‐based psychological therapy due to cognitive deficits (Adams & Boyd, ; Butz, Bowling, & Bliss, ; Sturmey, Lott, Laud, & Matson, ) with mental health interventions largely involving medication and behavioural techniques (Vereenooghe & Langdon, ). The need for adapting cognitive behaviour therapy (CBT) for adults with ID has been addressed (e.g., Willner & Lindsay, ), and recent studies have found CBT successful in treating mental health difficulties in adults with ID (e.g., Nicoll, Beail, & Saxon, ; Osugo & Cooper, ; Vereenooghe & Langdon, ), supporting its potential with younger age groups. This review seeks to consider how psychological therapy, specifically CBT, might best be adapted for children with ID.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of mental health difficulties in adults with ID (Cooper, Smiley, Finlayson, et al, 2007;Devine et al, 2010), there is substantial clinical and research interest in identifying effective treatments. Emerging evidence suggests that CBT can be effective (Osugo & Cooper, 2016;Vereenooghe & Langdon, 2013), yet there have been limited descriptions in the literature on the process of adapting cognitive challenging for adults with ID. Moreover, it has been noted that previous studies have mislabelled behavioural techniques as cognitive strategies (Sturmey, 2004) and that many references to cognitive challenging have instead described thought replacement strategies (Taylor et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders are common (Bailey & Andrews, ; Cooper, ; Cooper, Smiley, Morrison, Williamson, & Allan, ; Deb, Thomas, & Bright, ) and do not typically remit without intervention (Tonge & Einfeld, ), yet evidence‐based psychological treatments for anxiety disorders in people with ID are lacking (Koslowski et al, ; Osugo & Cooper, ; Unwin, Tsimopoulou, Kroese, & Azmi, ; Vereenooghe & Langdon, ). Research suggests that adults with predominately mild ID can benefit from psychological treatments such as cognitive behaviour therapy (CBT; Osugo & Cooper, ), particularly for depression and anger difficulties (Vereenooghe & Langdon, ); however, the evidence base is still in a nascent stage. In particular, there is variability in reporting in the literature on how CBT interventions are modified and implemented for adults with ID, which limits investigations into the efficacy of CBT for people with ID (Unwin et al, ; Vereenooghe & Langdon, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation